"Fischen und Fischergespräch und Anderes von Petar Hektorović aus Hvar": Humanität und Humanismus in der kroatischen Renaissance - Stagl-Škaro, Natalia (2021)
Petar Hektorović and his production, both material and Immaterial are here considered as a complex unity. His trilingual "Fishing and fishermen's conversation and other things" consists of sixteen differing texts. These are translated, annotated and put in context with each other.